Acrylamide formation and aroma evaluation of fried pepper sauce under different exogenous Maillard reaction conditions - Yuting Song; Zhuhong Ding; Yuzhu Peng; JiaYing Wang; Ting Zhang; Yihong Yu; Yi Wang (Food Chemistry: X, 2022)
To explore the impact of the Maillard reaction on fried pepper sauce (FPS) flavor and safety quality, acrylamide and volatile organic compounds (VOCs) were measured in FPS. Acrylamide was detected in 10 Maillard treated groups and a total of 110 VOCs were identified, mainly aldehydes, ketones, alcohols, acids, etc., but the content of each group differed. Partial least squares discriminant analysis showed that acrylamide in white sugar-sodium glutamate group and xylose-soy peptide group processing accumulated most acrylamide and least VOCs; Lactose-glycine, lactose-cysteine, lactose-soy peptide, and white sugar-glycine groups were positively correlated with typical Maillard reaction product (2,3-Dihydro-3,5-dihydroxy-6-methyl-4(H)-pyran-4-One); Xylose-glycine, xylose-cysteine, and white sugar-cysteine groups were weakly correlated with typical products, but positively correlated with most VOCs, whereas white sugar-cysteine group lipids showed high oxidation levels. Although white sugar-soy peptide group is not harmful on acrylamide, it has little correlation with VOCs with large responses. Conventional excipient group aroma is relatively simple with a fresh fatty taste, whereas xylose-glycine, xylose-cysteine, xylose-soy peptide, lactose-glycine, and white sugar-cysteine groups all present basic fresh and fatty tastes; lactose-cysteine group has a fruity base note; and lactose-soybean peptide, white sugar-glycine, and white sugar-soybean peptide groups have a fruity base note on an unpleasant fatty aroma. Therefore, processing different exogenous Maillard reaction substrates can achieve FPS aroma regulation and reduce acrylamide harm.